Comparison of the efficacy of the tumour necrosis factor α blocking agents adalimumab, etanercept, and infliximab when added to methotrexate in patients with active rheumatoid arthritis. (7th October 2003) - Hochberg, M C; Tracy, J K; Hawkins-Holt, M; Flores, R H
Abstract : Objective: To determine, using the method of adjusted indirect comparisons, whether there are differences in efficacy of tumour necrosis factor (TNFα) blocking agents, as measured by the rate ratios for American College of Rheumatology (ACR) 20, 50, and 70 responses, in patients with rheumatoid arthritis with an incomplete response to methotrexate. Methods: A systematic review was performed to identify placebo controlled trials of 24–30 weeks' duration of combination therapy that used a step-up approach with the addition of TNFα blocking agents to methotrexate. The method of "adjusted indirect comparisons" was used to compare results across trials to determine the relative risk for an ACR20 or 50 response. Results: Placebo controlled trials for adalimumab, etanercept, and infliximab provided data on ACR20 and 50 responses. Both the similarity of demographic and disease characteristics of patients at entry, and the homogeneity of response rates in the placebo groups across trials, suggested that comparing results across trials was valid. The relative risk for obtaining an ACR20 and 50 response derived from the adjusted indirect comparisons of the TNFα blocking agents did not significantly differ from unity. Conclusion: The analysis showed that the three currently marketed TNFα blocking agents have similarly efficacy when added to methotrexate in the treatment of patients with rheumatoid arthritis with active disease.